Pemberian Latihan Gerak Dalam Mengurangi Nyeri Osteoartritis Pada Lansia - Asrina Pitayanti; Fitria yuliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Joint pain is a disease that is familiar in everyday life. and mostly in elderly people who are close to joint pain disorders which is a degenerative disease. Apart from the age factor, there are many things that influence the rate at which joint pain occurs due to the fact that many elderly people do not control their lifestyle such as regular exercise, diet and so on. Pain often occurs in the hands or fingers, knees, hips and spine. This disease generally develops gradually and gets worse over time, disrupting the sufferer's ability to do physical activity. Methods of exercise therapy for osteoarthritis are therapy in the form of active movement exercises and in the form of exercises using resistance/weights which aim to train the muscles so that the muscles become relaxed, preventing limitations. movement, maintain muscle elasticity and increase muscle strength. Exercise therapy will minimize injury by strengthening the muscles supporting the joints, restoring strength and range of motion so that activities can be carried out as before. Activities that are beneficial for health should meet the FITT criteria (frequency, intensity, time, type). Frequency is how often the activity is done, intensity is how hard the activity is done, usually divided into low, medium and high intensity. Time refers to the duration of the activity and the type of physical activity carried out. Community service activities are aimed at all elderly people in order to increase knowledge and alternatives about non-pharmacological therapies that are relatively safe from side effects.